Improvement of the competitive organizational-economic model of disposal of agricultural land in Ukraine - Yarova, B. (Land Management, Cadastre and Land Monitoring, 2018)
Article 134 of the Land Code of Ukraine states that the sale and lease of land plots of state and communal property must take place at land auctions. However, the procedure for conducting them requires improvement and simplification.The procedure for the sale of land or rights to them on a competitive basis is established by Chapter 21 of the Land Code of Ukraine. However, in Articles 134-139 of the Civil Code, definitions are not fixed, such as "land auction", "land auction", "licitator", "lot", "starting price of lot", "selling price of lot", "participant's card", "information card ","guarantee payment", "a step of public auction", etc. The collisions between the two key concepts cause a number of inappropriateness that may adversely affect the application of land legislation. It would be expedient to define the basic concepts in the Land Code of Ukraine, which would make it impossible to manipulate and use differently in practice.The next thing I would like to draw attention to is the registration fee payment. Contribution, the size of not more than 50% of the subsistence minimum for able-bodied persons at the date of publication of the announcement of conducting land auctions. In order to solve this problem, it would be advisable to cancel the registration fee payment as a mandatory condition for participation in land trades.As you can see, too complicated mechanism for the conclusion of a contract, provided by the LCU, a number of inappropriateness, and this is until the recognition of trades such that did not happen, before canceling and canceling them.It deserves attention to the provisions of the Land Code of Ukraine, which establishes that land tenders are conducted not earlier than 30 days and not later than 90 days after the announcement of the announcement. However, there is a positive practice of applying the norms of the current legislation (the Law of Ukraine "On Mortgage"), where the auction is for two months.It would be advisable to supplement the content of the announcement of the bidding by the point "registration deadline for bidding", which will make it possible to prevent the deprivation of the right to participate in willing persons who do not have a detailed knowledge of the legally prescribed procedure. It would also be necessary to set a deadline for registration for participation no earlier than one hour before the start of the bidding. In this case, the applicant shall ensure the payment of a guarantee fee for participation in these public tenders no later than one day before the start of their conduct.The Land Code of Ukraine does not specify sanctions for failure to comply with the conditions and procedure for conducting land auctions. There is no indication of the consequences of not receiving an entrance ticket or information card, etc. This uncertainty may be the cause of challenging bids and contracts based on their results.The Land Code of Ukraine does not provide for the establishment at the legislative level of the percentage reduction in the initial price for repeated land tenders. It would be desirable to determine the mechanism of formation of the initial price in case of repeated auction in the form of an auction.The mechanisms of improvement of conducting land auctions in the form of an auction are proposed, which is based on simplification of its organizational principles and reduction of transaction costs of bidder. It is proved that the proposed organizational and economic model of land allocation for agricultural purposes, based on an improved mechanism for holding land auction in the form of an auction, will allow reducing the cost of this procedure to 50% of the subsistence minimum for able-bodied persons at the date of publication of the announcement of conducting land auctions.